Idea misji Boskiej jako faktu eklezjalnego w doktrynie encyklik misyjnych papieży przedsoborowych - Balwierz, Marian (Śląskie Studia Historyczno-Teologiczne, 1983)
The top priority of the practice before the theory of mission was an immutable principle for the Church of Jesus Christ in the two thousand years of her history. This rule was observed also by the Church in the modern process of development of the missionary activity during the last two centuries. No doubt, this development is an outcome of paying more and more attention to this, that the missionary work is as well an ecclesiastical fact as it is a charismatic one. Such an idea has theologically slowly grown up in the papal teaching about some real problems regarding the missionary practice of the Church. The Teaching Church developed the theologically fundamental thoughts of this ecclesiastical vision of the mission when it pointed do the ways of solving these problems. Such a process can be perfectly observed in the whole of the missionary teaching of the pre-conciliar popes. The idea of God’s mission which is the ecclesiastical fact, is not a statical component of the doctrine enclosed in the missionary encyclicals of the preconciliar popes. Before the Second Vatican Council, this idea was perpetually developed in this teaching by the ways of going deeply into particular questions connected with it. The popes also explicated a lot of essential thoughts of the theology of mission in the course of this evolution. These particular ideas of the pre-conciliar missiology converge in the three main points of the papal teaching from that period, namely in the teaching about the religious nature of the missionary activity, about its ecclesiastical dimension and about the Divine character of the mission of the Church. Together with other questions mentioned by the pre-conciliar popes, those ideas form a fundamental schedule of the Catholic theology of mission up to these days. During a further evolution of this branch of theology, the Teaching Church has first of all integrated those thoughts into a principal idea of the Church’s dynamism. In the pre-conciliar period, a development of the theological thought about a strict connection between the missionary task of the Church and the Christian faith, was a source of the papal teaching about the religious nature of the missionary activity. This development was grounded on a specification of the papal teaching about the permanence of the mission, its apostolical dimension and its connections with the Salvation of Christ. A subtle maturation of some papal thoughts about the ecclesiastical dimension of the mission of the Church was a direct result of this theological evolution. It is obvious, that the less speculative question of the ecclesiastical dimension of the missionary activity was developed in a more analitycal way by the very practical statements of the pre-conciliar popes about the missionary problems. A generative dynamism of the faith is a source of the ecclesiastical dimension of the missionary activity. When the pre-conciliar popes developed the thoughts about the faith, the mission and the Church, they also brought up the teaching about the missionary activity tending towards an incorporation of the Church in the native culture of the evangelized people. An incorporating accommodation remains the essence of this process of the transplantation of Christ’s Church. The Teaching Church slowly accomplished in that theological context a great change of the whole perspective which forms its view of the People of God of the New Covenant. This change consists in a replacement of the vision of Christ’s universal Church by the vision of some particular Churches. The new ecclesiological perspective generates in the theology of mission an emphasis on the connections of the source of the missionary activity, its exact process and its aim with an eschatological tension, which exists between Christ’s universal Church and the individual local Churches. Such a thought remains one of the most significant ideas in the theology of mission elaborated by the pre-conciliar Church. An idea of the Divine character of the Church’s mission was developed in the indirect way by the pre-conciliar popes. The theological thought about the one mission given to the whole Church of Christ was elaborated in the context of the papal teaching about the responsibility of all the Church’s members for the missionary work. When the popes Benedict XV and Pius XI carried on the idea of the only one mission in their teaching about the obligations of the missionaries, they both presented a synthesis of some earlier thoughts about the Divine character of the mission of the Church. These two popes taught, that the Almighty God is in the beginning of the Church’s mission. He also works by his grace in the exact process of the evangelization of the people and He gives it the whole of its efficacy. The other pre-conciliar popes also knew these thoughts, because since the very beginning of their missionary teaching, they all united some particular parts of the evangelizing process with the works of the individual Persons of the Holy Trinity. This trinitarian view of the mission of the Church is also hidden in the papal pre-conciliar teaching about love, which is the ultimate source of the vivacity of the missionary work. There is no serious doubt that the missionary teaching of the pre-conciliar popes is more practical than theoretical. But this practical nature only gives a pastoral character to this teaching. It does not deprive it of its very deep theological thoughts. So those popes spoke out the real theological consciousness of the missionary Church without any unnecessary discussion about the different opinions of the various theological schools. It was observed before and it has been also confirmed by this study. The missionary teaching of the pre-conciliar popes became an official teaching of the Church of Christ in that way.